Horizontal transmission of de novo hepatitis B between spouses: A case report. Issue 8 (14th October 2014) - Mawatari, Seiichi; Uto, Hirofumi; Moriuchi, Akihiro; Tabu, Kazuaki; Muromachi, Kaori; Tabu, Eriko; Oda, Kohei; Imanaka, Dai; Oshige, Akihiko; Nakazawa, Junichi; Kumagai, Kotaro; Tamai, Tsutomu; et al.
<x xml:space="preserve">Abstract</x> We report a female patient with acute hepatitis B due to horizontal transmission of hepatitis B virus from her husband, who suffered from de novo hepatitis B. A 48‐year‐old man underwent peripheral blood stem cell transplantation (PBSCT) for adult T‐cell leukemia/lymphoma. Nine months after the initial treatment, he was referred to our hospital because of jaundice. Laboratory data showed elevated serum aminotransferase levels and hepatitis B surface antigen (HBsAg) positivity. We diagnosed de novo hepatitis B because a pre‐PBSCT serum sample was negative for HBsAg and positive for anti‐hepatitis B core antibody (HBcAb). His liver function improved with entecavir therapy. Two months after his diagnosis of hepatitis B, his 31‐year‐old wife was admitted with fever and appetite loss. She was diagnosed with acute hepatitis B because of increased serum aminotransferase levels and HBsAg and immunoglobulin M HBcAb positivity. Sequencing of HBV DNA in the serum obtained from both patients showed 99.9% homology. Therefore, we diagnosed her acute hepatitis B as due to horizontal transmission of de novo hepatitis B from her husband. HBV derived from de novo hepatitis B should be considered a potential source of infection, although intrafamilial transmission of de novo hepatitis B is rare.